Rearrangment of Archives Handling at Human Resources Department General Affair PT Beton Elemenindo Perkasa Batujajar - Yoseva Halalas Mora Sitohang; Tintin Suhaeni (Ebiz Prima Nusa, 2022)
An archive is a collection of documents, documents, or files that have value for the company. The role of archives in a company is as a memory center, a controlling tool, a source of information used by companies to carry out analysis, planning activities, development, weighing in decision making, problem formulation, making attachments, accountability, assessment and control as precisely as possible. Archival rearrangement is the rearrangement of information and archive forms for the benefit of archive retrieval. The condition of handling archives in the Human Resources Department of PT Beton Elemenindo Perkasa can be said to be less precise, this can be seen from the number of missing archives, irregularly stored archives, there are still archives that use inappropriate storage systems, lack of equipment and supplies used to store archives. files. This phenomenon causes difficulties in the process of finding the archives needed by the company, so that it can hinder the company's work. Therefore, it is necessary to reorganize the archive handling project at the Human Resources DepartmentGeneral Affair of PT Beton Elemenindo Perkasa Batujajar by updating the storage system, storage procedures, archive borrowing procedures, archive discovery procedures, and adding archive facilities. The purpose of the archive handling reorganization project is to optimize the handling of existing records so that they are more effective and efficient. This project has been tested on June 3rd, 2021 with related parties, namely the Human Resources Department-General Affair Staff who doubles as archivist and the manager of the department. Based on the trials that have been carried out on this project, it can be said that the archive handling project at the Human Resources Department-General Affairs PT Beton Elemenindo Perkasa Batujajar is appropriate and very helpful for administrative staff in handling existing archives.